The metaverse and career development : applications, implications and future directions - Priyashantha, K. G. (Routledge research in human resource management, 2026)
This book explores how the Metaverse may be applied to career development practices.Beginning with a systematic review of empirical literature to foreground tested Metaverse applications in both workplace and educational settings, the book provides a framework for discussing possible Metaverse applications through five key career stages: Growth, exploration, establishment, maintenance, and disengagement. It then provides best practices, policy considerations, and implementation guidelines for organizations and educational institutions. Ethical considerations, including privacy, data security, digital divide, and psychological impacts of prolonged immersion in virtual environments, are also discussed.This book will interest scholars of digital human resource management, human resource development, and career management. Its practical suggestions may also interest HR practitioners and policymakers.